The Effect of Prevention and Management Protocols on Low Back Pain in Athletes: A Systematic Review - Mohammad Hosein Alizadeh; Behrouz Jafari; Mohammad Rahim Amiri (Physical Treatments, 2022)
Purpose: Low back pain (LBP) is the most common musculoskeletal disorder reported in the community, leading to chronic pain and disability. This review aims to determine the effectiveness of prevention and management protocols on LBP in athletes. Methods: Searches were conducted from 2010 to 2022 from international databases, including Google Scholar, Science Direct, and PubMed using keywords related to back pain in athletes. Randomized controlled trials (RCTs) presenting the prevention and management protocol for back pain of athletes were included in this review. The physiotherapy evidence database (PEDro) scale was used to check the quality of articles. Results: Finally, 16 articles with 1,317 subjects met the inclusion criteria. These studies have mainly focused on the effect of taping, cognitive functional approach, movement patterns, conditioning, lifestyle, motor control, segmental motion, isokinetic, core stabilization, virtual reality training, dynamic and static stretching, Mézières method, functional movement screen, and semi-customized exercises in athletes at risk of LBP. The positive effect of stability and cognitive exercises were documented. Conclusion: The deep and superficial muscle integration exercises by correcting the body posture and correct muscle calling had the greatest effect on the balance of the muscles.